Using micro-CT techniques to explore the role of sex and hair in the functional morphology of bumblebee (Bombus terrestris) ocelli. (May 2019) - Wilby, David; Aarts, Tobio; Tichit, Pierre; Bodey, Andrew; Rau, Christoph; Taylor, Gavin; Baird, Emily
Abstract: Many insects have triplets of camera type eyes, called ocelli, whose function remains unclear for most species. Here, we investigate the ocelli of the bumblebee, Bombus terrestris, using reconstructed 3D data from X-ray microtomography scans combined with computational ray-tracing simulations. This method enables us, not only to predict the visual fields of the ocelli, but to explore for the first time the effect that hair has on them as well as the difference between worker female and male ocelli. We find that bumblebee ocellar fields of view are directed forward and dorsally, incorporating the horizon as well as the sky. There is substantial binocular overlap between the median and lateral ocelli, but no overlap between the two lateral ocelli. Hairs in both workers and males occlude the ocellar field of view, mostly laterally in the worker median ocellus and dorsally in the lateral ocelli. There is little to no sexual dimorphism in the ocellar visual field, suggesting that in B. terrestris they confer no advantage to mating strategies. We compare our results with published observations for the visual fields of compound eyes in the same species as well as with the ocellar vision of other bee and insect species.